2020
DOI: 10.1128/cmr.00074-20
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Coronavirus-Induced Acute Respiratory Distress Syndrome (ARDS): Potential Infection-Associated Hemophagocytic Lymphohistiocytosis

Abstract: SUMMARY The outbreak of coronavirus disease 2019 (COVID-19) in December 2019 in Wuhan, China, introduced the third highly pathogenic coronavirus into humans in the 21st century. Scientific advance after the severe acute respiratory syndrome coronavirus (SARS-CoV) epidemic and Middle East respiratory syndrome coronavirus (MERS-CoV) emergence enabled clinicians to understand the epidemiology and pathophysiology of SARS-CoV-2. In this review, we summarize and discuss the epidemiology, clinical features, and virol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 207 publications
(277 reference statements)
1
31
0
3
Order By: Relevance
“…It has been suggested that a subgroup of patients suffering from severe COVID-19 pneumonia could develop sHLH. 2 32 33 These patients meet the laboratory parameters necessary to the diagnosis of sHLH such as elevated CPR and hyperferritinemia and other clinical conditions including abnormal liver function and coagulopathy. 34 Previous related viruses as SARS-CoV and MERS-CoV showed similar clinical course than SARS-CoV-2, although in the first two, the proportion of patients with fatal evolution was higher, especially in MERS-COV.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a subgroup of patients suffering from severe COVID-19 pneumonia could develop sHLH. 2 32 33 These patients meet the laboratory parameters necessary to the diagnosis of sHLH such as elevated CPR and hyperferritinemia and other clinical conditions including abnormal liver function and coagulopathy. 34 Previous related viruses as SARS-CoV and MERS-CoV showed similar clinical course than SARS-CoV-2, although in the first two, the proportion of patients with fatal evolution was higher, especially in MERS-COV.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, an increased neutrophil/ lymphocyte ratio has been determined to be an independent risk factor for severe disease (35). NKG2A expression induced by SARS-CoV-2 may be associated with early functional depletion of cytotoxic lymphocytes such as cytotoxic T lymphocytes and NK cells, leading to disease progression (30,31).…”
Section: Innate Immune Responsementioning
confidence: 99%
“…Клинические проявления гемофагоцитарного синдрома трудно различить в картине тяжело протекающего основного заболевания, поэтому о его частоте при COVID-19 судить трудно. Однако складывается впечатление, что сосуществование синдрома и COVID-19, описанное не только в отдельных случаях, но и в сериях наблюдений, является не случайным явлением, а патогенетически обусловленной закономерностью [110,[113][114][115].…”
Section: актуальная проблемаunclassified